A cell‐penetrating CD40‐TRAF2, 3 blocking peptide diminishes inflammation and neuronal loss after ischemia/reperfusion. Issue 3 (6th March 2021) - Portillo, Jose‐Andres C.; Yu, Jin‐Sang; Hansen, Samuel; Kern, Timothy S.; Subauste, M. Cecilia; Subauste, Carlos S.
Abstract: While the administration of anti‐CD154 mAbs in mice validated the CD40‐CD154 pathway as a target against inflammatory disorders, this approach caused thromboembolism in humans (unrelated to CD40 inhibition) and is expected to predispose to opportunistic infections. There is a need for alternative approaches to inhibit CD40 that avoid these complications. CD40 signals through TRAF2, 3 and TRAF6‐binding sites. Given that CD40‐TRAF6 is the pathway that stimulates responses key for cell‐mediated immunity against opportunistic pathogens, we examined the effects of pharmacologic inhibition of CD40‐TRAF2, 3 signaling. We used a model of ischemia/reperfusion (I/R)‐induced retinopathy, a CD40‐driven inflammatory disorder. Intravitreal administration of a cell‐penetrating CD40‐TRAF2, 3 blocking peptide impaired ICAM‐1 upregulation in retinal endothelial cells and CXCL1 upregulation in endothelial and Müller cells. The peptide reduced leukocyte infiltration, upregulation of NOS2/COX‐2/TNF‐α/IL‐1β, and ameliorated neuronal loss, effects that mimic those observed after I/R in Cd40−/− mice. While a cell‐penetrating CD40‐TRAF6 blocking peptide also diminished I/R‐induced inflammation, this peptide (but not the CD40‐TRAF2, 3 blocking peptide) impaired control of the opportunistic pathogen Toxoplasma gondii in the retina. Thus, inhibition of the CD40‐TRAF2, 3 pathway is a novel and potent approach to reduce CD40‐induced inflammation, while likely diminishing the risk of opportunistic infections that would otherwise accompany CD40 inhibition.